The Utility of Computed Tomography and Intrathecal Fluorescein in the Management of Cerebrospinal Fluid Leak. Issue 3 (May 2020) - Flynn, John P.; Pavelonis, Anna; Ledbetter, Luke; Bhalla, Vidur; Alvi, Sameer A.; Chiu, Alexander G.; Villwock, Jennifer
Background: Intrathecal fluorescein (IF) has become a common tool for localization of cerebrospinal fluid (CSF) leak, but despite frequent use, IF lacks Food and Drug Administration approval. The diagnostic ability of high-resolution computed tomography (HRCT) has increased over several decades. Subspecialized rhinology training within otolaryngology has, similarly, allowed for dedicated skull base surgeons to become more adept at CSF leak localization. Objectives: To evaluate the utility of HRCT and IF in CSF leak localization. To identify certain patient populations in which IF has added utility. To analyze the ability of fellowship-trained neuroradiologist and rhinologist to localize CSF leak sites. Methods: Data were collected from a single, tertiary care academic institution. Patients admitted for CSF leak between 2003 and 2016 were included. Diagnostic yield of preoperative imaging and IF for identification of leak site was analyzed. Fellowship-trained neuroradiologist and rhinologist performed retrospective review of CT imaging and identified CSF leak sites. Results: One hundred and two patients underwent CSF leak repair. Skull base defects were preoperatively localized to exact sinus on imaging report in 67% of patients. Preoperative imaging stratified by CT slice thickness of 0.625 mm identified leak site in 88.9% of cases. Blinded retrospective review by a neuroradiologist and rhinologist was able to localize the CSF leak to the correct or adjacent sinus in >80% of cases. IF was useful for intraoperative localization in 73% of cases. When preoperative imaging failed at leak site localization, IF was able to correctly identify leak site in 75% of cases. Conclusions: The diagnostic yield of IF and CT imaging was equivalent, with each modality localizing leak site approximately two-thirds of the time. CT imaging with 0.625 mm slice thickness proved more efficacious in identification of skull base defects. IF demonstrated increased utility in instances where preoperative imaging has failed at leak site identification.